The Stress-Strength Model: R=P(Y < X) Gamma Case by Mathematica - Hussain, Ehtesham; Ahsanuddin, Muhammad (European Scientific Journal, ESJ, 2019)
In this paper, we considered the estimation of R=P(Y<X), dubbed as Stress-Strength Model (SSM), in a framework of gamma distribution with unknown scale and shape parameters. This is not an easy computing problem in conventional mathematics. For such problems, a very important option is using a Mathematica software, which has been employed to obtain solutions to this problem.